In Search of "Capital Crunch" : Supply Factors Behind the Credit Slowdown in Japan - Woo, David (IMF Working Papers; Working Paper ;, 1999)
The seeming failure of loose monetary policy to reactivate Japan's economy has led some observers to suggest that the usual credit channels through which monetary policy affects the real economy are blocked, and this because of a pervasive shortage of bank capital that has induced a leftward shift in the supply of bank credit: the so called credit crunch hypothesis. This paper finds support for the hypothesis in the 1997 bank data-a year during which the landscape of the Japanese financial system was changed fundamentally-but finds no, or even contrary, evidence, for most of the 1990's.